Response of Siratro (Macroptilium atropurpureum Urb. Rabaceae) to Vesicular-arbuscular Mycorrhizal Fungi and Rhizobium sp. in Sterilized Soil - S., Greep; T., Muthukumar; K., Udaiyan; V., Narmatha Bai (Universiti Putra Malaysia Press, 1997)
The effect of inoculation of six species of vesicular-arbuscular mycorrhizal fungi viz., Gigaspora margarita, Glomus mosseae, G. monosporum, G. versiformis, G. fasciculatum, G. deserticola and Rhizobium sp. on growth and NPK content in siratro (Macroptilium atropurpureum) was studied. The mycorrhizal species were isolated from the rhizosphere forest soils of the Western Ghats and multiplied in pot culture with Sorghum bicolor as the host plant. Rhizobium sp. isolated from fresh nodules of siratro was cultured and maintained in yeast extract mannitol broth. The influence of VAM fungi and Rhizobium sp. either singly or in combination on growth and nutrient contents of siratro showed statistically significant increase after only 60 days of plant growth. Dual inoculation with VAM fungi and Rhizobium increased plant nodule number and tissue NPK content. Highest growth and nutrient content were exhibited by plants inoculated with Rhizobium together with multiple VAM fungi.